Changes in markers of oxidative stress and DNA damage in human visceral adipose tissue from subjects with obesity and type 2 diabetes - Sarah Prior (Diabetes Research and Clinical Practice, 2014)
AimsIn the past 30 years, prevalence of obesity has almost trebled resulting in an increased incidence of type 2 diabetes mellitus and other co-morbidities. Visceral adipose tissue is believed to play a vital role, but underlying mechanisms remain unclear. Our aim was to investigate changes in markers of oxidative damage in human visceral adipose tissue to determine levels of oxidative burden that may be attributed to obesity and/or diabetes.MethodsVisceral adipose tissue samples from 61 subjects undergoing abdominal surgery grouped as lean, obese and obese with type 2 diabetes mellitus, were examined using 3 different markers of oxidative stress. Malondialdehyde (MDA) concentration was measured as a marker of lipid peroxidation, telomere length and Comet assay as markers of oxidative DNA damage.ResultsNo significant difference in MDA concentration, telomere length and DNA damage was observed between groups, although longer telomere lengths were seen in the obese with diabetes group compared to the obese group (P < 0.05). Lower MDA concentration and longer telomere length were seen in subjects with diabetes compared to those without (P < 0.05). DNA damage, analysed via Comet assay, was significantly lower in subjects with diabetes compared to those without (P < 0.05).ConclusionA paradoxical decrease in oxidative stress and DNA damage was observed in samples from subjects with type 2 diabetes mellitus. Further work is required to investigate this further, however this phenomenon may be due to an up regulation of antioxidant defences in adipose tissue.